Hiring chains and the dynamic behavior of job and worker flows - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2011)
In this paper, I discuss three sets of links which I uncover in the data on aggregate US job and worker flows. Job flows are strongly related to aggregate employment growth, while worker flows are strongly related to employment growth and the unemployment rate. I show that a simple frictionless business cycle model with heterogeneity and a simple form of on-the-job search can explain these links. Job flows respond simply to the cross-section of firm growth, which responds to aggregate employment growth. Worker flows are related to both employment growth and the unemployment rate, and quits and hires are particularly tightly related to each other. Quits and hires interact to form a hiring chain-hires beget quits through on-the-job search, and quits beget hires to replace quitters. High unemployment crowds out quits, shortens the hiring chain, reduces the number of hires, and also results in an elevated layoff rate. The simple hiring chain model fits the data surprisingly well.
Keywords: E32; J63; J21; 330; Job flows; worker flows; heterogeneity; on-the-job search; hiring chain; Arbeitsmobilität; Arbeitsnachfrage; Konjunktur; Arbeitsuche; Personalabbau; Schätzung; USA